Initial experience with pulsed field ablation for atrial fibrillation - Magni, Federico T.; Mulder, Bart A.; Groenveld, Hessel F.; Wiesfeld, Ans C. P.; Tieleman, Robert G.; Cox, Moniek G.; Van Gelder, Isabelle C.; Smilde, Tom; Tan, Eng S.; Rienstra, Michiel; Blaauw, Yuri (Frontiers in Cardiovascular Medicine, 2022)
Introduction Pulsed field ablation (PFA) was recently introduced for the treatment of symptomatic atrial fibrillation (AF) with the claim of selectively ablating the myocardium while sparing surrounding tissues. We present our initial experience with a PFA catheter for pulmonary vein isolation (PVI) and describe procedural findings and peri-procedural safety of the first 100 patients. Materials and methods We investigated 100 patients treated for symptomatic AF using the FARAWAVE PFA catheter (Farapulse, Menlo Park, CA, USA) between July 2021 and March 2022. Procedure workflow and electrophysiological findings at the time of ablation, peri-procedural complications, and operator learning curves are described. Results The mean age of patients was 62.9 ± 9.4 years, 62% were male subjects and 80% had paroxysmal AF. The median CHA2DS2-VASc score was 1.5 (IQR: 1.0–2.0) and the mean left atrial volume index was 35.7 ± 9.6 ml/m2. In 88 (88%) patients, PVI alone was performed and in 12 (12%) patients additional ablation of the posterior wall was performed. 3D-electroanatomic mapping was performed in 18 (18%) patients. Procedures without mapping lasted for 52.3 ± 16.6 min. The mean number of applications per pulmonary vein (PV) was 8.1 ± 0.6. In all patients (100%), all PVs were confirmed to be isolated. The learning curves of the two operators who performed > 20 procedures showed a negligible variation of performance over time and practice did not significantly predict procedure time [Operator 1 (senior): R2 = 0.034, p = 0.35; Operator 2 (junior): R2 = 0.004, p = 0.73]. There was no difference between the procedure times between senior and junior operators (Operator 1: 46.9 ± 9.7 min vs. Operator 2: 45.9 ± 9.9 min; p = 0.73). The only complications observed were two cases of bleeding at the site of percutaneous access. Conclusion Our initial experience shows that use of the PFA catheter for pulmonary vein isolation (PVI) is safe, fast, and easy to learn.